Glassware and glassworking in Thessaloniki : 1st century BC - 6th century AD - Antonaras, Anastassios C., (Archaeopress Roman archaeology ;, 2017)
A detailed examination of the production of glass and glass vessels in the eastern Mediterranean from the Hellenistic Age to the Early Christian period, analysing production techniques and decoration.